2016
DOI: 10.1371/journal.pntd.0004895
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Diversity of Pathogenic Leptospira Species in Peri-domestic Surface Waters from South Central Chile

Abstract: BackgroundLeptospirosis is a neglected zoonosis affecting animals and humans caused by infection with Leptospira. The bacteria can survive outside of hosts for long periods of time in soil and water. While identification of Leptospira species from human cases and animal reservoirs are increasingly reported, little is known about the diversity of pathogenic Leptospira species in the environment and how surveillance of the environment might be used for monitoring and controlling disease.Methods and FindingsWater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 45 publications
1
37
2
Order By: Relevance
“…Studies have identified DNA sequences of Leptospira from the P1 subclade in drinking water (for human or for animals) samples [79][80][81][82]. This suggested a significant health concern and opened the way to consider Leptospira in studies on the potential risks associated with drinking water [83,84].…”
Section: Leptospira In Water Environments 331 Occurrence Of Leptospmentioning
confidence: 99%
“…Studies have identified DNA sequences of Leptospira from the P1 subclade in drinking water (for human or for animals) samples [79][80][81][82]. This suggested a significant health concern and opened the way to consider Leptospira in studies on the potential risks associated with drinking water [83,84].…”
Section: Leptospira In Water Environments 331 Occurrence Of Leptospmentioning
confidence: 99%
“…Saprophytic leptospires are normal inhabitants of freshwater, which do not involve any sanitary risk. However, there has also been evidence of pathogenic leptospires from drinking water for animals (Calderon et al, 2014;Muñoz-Zanzi et al, 2014;Mason et al, 2016;Kurilung et al, 2017), but also for humans (Muñoz-Zanzi et al, 2014;Mason et al, 2016). Very interestingly, a shotgun metagenomics study retrieved a Leptospira spp.…”
Section: Drinking Watermentioning
confidence: 99%
“…Reservoir animals shed Leptospira in their urine and humans are infected with the organism by contact with contaminated urine, water, and soil through the skin and mucous membranes . Pathogenic Leptospira have been isolated from patients, reservoir animals, and environmental specimens such as water and soil . However, the abundance of environmental bacteria in water and soil makes isolation difficult.…”
Section: Culture‐positivity Rate Of Leptospira In Environmental Watermentioning
confidence: 99%
“…2 Pathogenic Leptospira have been isolated from patients, reservoir animals, and environmental specimens such as water and soil. [3][4][5][6] However, the abundance of environmental bacteria in water and soil makes isolation difficult. Chakraborty et al developed a novel selective medium composed of five antimicrobial agents, namely sulfamethoxazole, trimethoprim, amphotericin B, fosfomycin, and 5-fluorouracil, which are abbreviated as STAFF.…”
mentioning
confidence: 99%